(untitled) - Riordan, Rick (New York, 2006)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Poseidon (Greek deity); Fiction; Gods, Greek; Fiction; Camps; Fathers and sons; Friendship; Fiction; Fiction; Poseidon (Greek deity); Fiction; Mythology, Greek; Fathers and sons; Juvenile fiction; Fiction; Juvenile fiction; Friendship; Juvenile fiction; Camps; Juvenile fiction; Gods, Greek; Juvenile fiction; Mythology, Greek; Juvenile fiction; Greek junior fantasy